Homo‐ and Heteroleptic Copper(I) Complexes with Diazabutadiene Ligands: Synthesis, Solution‐ and Solid‐State Structural Studies. Issue 28 (29th August 2016) - Zelenay, Benjamin; Frutos‐Pedreño, Roberto; Markalain‐Barta, Jordi; Vega‐Isa, Esmeralda; White, Andrew J. P.; Díez‐González, Silvia
Abstract : The preparation of novel copper(I) complexes of diazabutadiene (DAB) ligands with aliphatic backbones is reported. [Cu(DAB R )2 ](BF4 ), [Cu(DAB R )(NCMe)2 ](BF4 ) and [CuCl(DAB R )] are easily synthesised and air‐stable. These complexes, which remain scarce in the literature, have been fully characterised, and their behaviour both in the solid state as well as in solution has been studied by means of X‐ray crystallography, NMR and UV/Vis spectroscopy. Abstract : The preparation of novel copper(I) complexes with aliphatic diazabutadiene (DAB) ligands is reported. [Cu(DAB R )2 ](BF4 ), [Cu(DAB R )(NCMe)4 ](BF4 ) and [CuCl(DAB R )] are easily synthesised and air‐stable. These complexes, which remain scarce in the literature, were fully characterised, and their behaviour both in the solid state as well as in solution has been studied by means of X‐ray crystallography and UV/Vis spectroscopy.